Combating Human Trafficking and Exploitation and Protection of Victims’ Rights in the Penitentiary System (Bulletin of Yerevan University C: Jurisprudence, 2025)
The article aims to present the manifestations of human trafficking and exploitation in the penitentiary system, the mechanisms for identifying such cases, the scope of victims’ rights and the obligations of the state. Emphasizing the importance of prison work in terms of rehabilitation and resocialization of individuals, it was underlined that the state, in particular, the prison administration, must take all necessary steps to exclude human trafficking and exploitation, considering its manifestation as a failure to fulfil the obligations of the state and a gross violation of human rights. As a result of the research, recommendations were presented aimed at addressing human trafficking and exploitation in the prison system. These include the introduction of a mechanism for identifying such cases, supporting and protecting victims, referrals and cooperation with other bodies, the inclusion of specific criteria for this issue in the general risk and needs assessment tool, etc. The importance of combating any manifestation of human trafficking and exploitation by the prison administration or peers deprived of liberty within the prison was emphasized.